A class of low‐cost alternatives to kifunensine for increasing high mannose N‐linked glycosylation for monoclonal antibody production in Chinese hamster ovary cells. (22nd September 2020) - Brantley, Timothy J.; Mitchelson, Fernie G.; Khattak, Sarwat F.
Abstract: N‐linked glycosylation of therapeutic monoclonal antibodies is an important product quality attribute for drug safety and efficacy. An increase in the percent of high mannose N‐linked glycosylation may be required for drug efficacy or to match the glycosylation profile of the innovator drug during the development of a biosimilar. In this study, the addition of several chemical additives to a cell culture process resulted in high mannose N‐glycans on monoclonal antibodies produced by Chinese hamster ovary (CHO) cells without impacting cell culture performance. The additives, which include known mannosidase inhibitors (kifunensine and deoxymannojirimycin) as well as novel inhibitors (tris, bis–tris, and 1‐amino‐1‐methyl‐1, 3‐propanediol), contain one similar molecular structure: 2‐amino‐1, 3‐propanediol, commonly referred to as serinol. The shared chemical structure provides insight into the binding and inhibition of mannosidase in CHO cells. One of the novel inhibitors, tris, is safer compared to kifunensine, 35x as cost‐effective, and stable at room temperature. In addition, tris and bis–tris provide multiple low‐cost alternatives to kifunensine for manipulating glycosylation in monoclonal antibody production in a cell culture process with minimal impact to productivity or cell health.